2017
DOI: 10.1103/physrevlett.119.257202
|View full text |Cite
|
Sign up to set email alerts
|

Fracton Topological Phases from Strongly Coupled Spin Chains

Abstract: We provide a new perspective on fracton topological phases, a class of three-dimensional topologically ordered phases with unconventional fractionalized excitations that are either completely immobile or only mobile along particular lines or planes. We demonstrate that a wide range of these fracton phases can be constructed by strongly coupling mutually intersecting spin chains and explain via a concrete example how such a coupled-spinchain construction illuminates the generic properties of a fracton phase. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 21 publications
1
58
0
Order By: Relevance
“…While the dual representations given by (21) and (24) are written in terms of classical variables, the same bond algebra is achieved if each classical variable is thought of as a σ z operator. This representation of the duality allows us to estimate (71) by calculating the corresponding autocorrelations of simple Ising models using Glauber dynamics [75]:…”
Section: Dynamics Of the X-cube Model At Finite Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…While the dual representations given by (21) and (24) are written in terms of classical variables, the same bond algebra is achieved if each classical variable is thought of as a σ z operator. This representation of the duality allows us to estimate (71) by calculating the corresponding autocorrelations of simple Ising models using Glauber dynamics [75]:…”
Section: Dynamics Of the X-cube Model At Finite Temperaturementioning
confidence: 99%
“…More recently, various quantum spin models believed to exhibit "fracton topological order" [21,22,23,24,25,26,27,28,29,30,31,32,33,34,35] were studied. Fracton topological order is a proposed state of matter in which fundamental excitations, termed "fractons", exhibit rich behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Constrained dynamics occurs naturally in so-called fracton systems, which are characterized by the existence of excitations that exhibit restricted mobility [47,48]. On one hand, these systems have been studied in threedimensional exactly-solvable lattice models with discrete symmetries, where fractons are created on the corners of a membrane or fractal operator [48][49][50][51][52][53]. On the other hand, different approaches for fractons with U(1) symmetry have shown that their mobility constraints are related to the conservation of the dipole moment which localizes isolated charged excitations.…”
Section: Introductionmentioning
confidence: 99%
“…A new chapter in the book of three-dimensional (3D) quantum phases of matter was opened with the discovery of fracton models [1][2][3][4][5][6][7][8], characterized by the presence of topological excitations with restricted mobility. These peculiar particles have attracted significant recent interest, thereby revealing intriguing connections to quantum information processing [9][10][11][12], topological order [13][14][15][16][17][18][19][20][21][22], sub-system symmetries [23][24][25][26][27][28][29][30], and slow quantum dynamics [1,3,[31][32][33]. Much of the phenomenology of fractons can also be realized in tensor gauge theories [34][35][36][37][38][39][40][41][42][43][44] with higher moment conservation laws, unveiling further connections of fractons with elasticity …”
Section: Introductionmentioning
confidence: 99%